Enhanced Electrochemical Properties of LiNi0.8Co0.1Mn0.1O2 at Elevated Temperature by Simultaneous Structure and Interface Regulating. Issue 8 (29th April 2019) - Feng, Ze; Huang, Xiaobing; Rajagopalan, Ranjusha; Tang, Yougen; Peng, Zhiguang; Wang, Haiyan
Abstract : Inferior cycling stability at elevated temperature is a big challenge for the commercial application of nickel-rich cathode materials because more serious phase transition, transition metal ion dissolution and side reaction of interface happen at elevated temperature than at room temperature. In the present work, strategies of element doping and surface coating are utilized together to stabilize the structure and interface electrochemistry. We successfully synthesized a Zr-doped and LiAlO2 -Al2 O3 coated LiNi0.8 Co0.1 Mn0.1 O2 material by a simple ball milling and wet chemical method. Owing to the synergistic effect of Zr doping and dual LiAlO2 -Al2 O3 coating, when cycled at 50°C, the modified LiNi0.8 Co0.1 Mn0.1 O2 sample exhibited significantly improved cycling stability with a capacity retention of over 96.8% after 60 cycles at a current rate of 1C, while the pristine sample could only retain a capacity of 73.3%. This improved electrochemical performance can be attributed to the effective doping and coating technique employed to the LiNi0.8 Co0.1 Mn0.1 O2 sample. The Zr doping is beneficial to reduce cation mixing and suppress the phase transition, while the LiAlO2 -Al2 O3 coating helps to enhance the protection of the electrode/electrolyte interface and reduce the transition metal ion dissolution.